Applying Effective Software for Controlling Computers Remotely - Mohammad, Marwa (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Today, many educational institutes, labs, houses or organisations have their private Local Area Network (LAN), so they need to monitor employees, students in exams or machines which are working on the network. This paper aims to design and implement efficient application that can be used to track everyone who is working between 1-10 users (operating systems) on LAN network remotely; so access PC, Mac and Linux. In other words, it can monitor screens remotely, send a warning message and shutdown system. Including, it operates at low-cost, enables daily using in the services of all scales; and provide the network performance simultaneously. The implementation has achieved using Front end- JDK, JAVA language, Windows 7, 8, and10, Visio, Wireshark, Task manager, chart expert, Microsoft excel, ten computers, Ethernet & Wireless of LAN network, etc. This software has applied in real-world in students examinations at three schools in Iraq. As a result, this software eligible to allocate the task to clients to restrict them from misusing the resources. As well as, automates lab and monitor attendance with performance analysis.